Digital economy enables common prosperity: Analysis of mediating and moderating effects based on green finance and environmental pollution - Zhang, Jie; Qian, Fangbin (Frontiers in Energy Research, 2023)
This study aims to explore the impact of the digital economy on common prosperity. For this reason, a bidirectional fixed effect model based on panel data of 30 provinces (cities and autonomous regions) in China is empirically tested. The results show that the digital economy can significantly improve the level of common prosperity, and has a positive impact on green and sustainable economic activities such as promoting environmental improvement, coping with climate change and resource conservation and efficient utilization, which is still valid after a series of robustness tests. At the same time, it proves that green finance undertakes a partial mediating effect in this model and that the environmental pollution index has a negative moderating effect. The analysis of regional heterogeneity shows that the enabling effect of the digital economy on common prosperity is more significant in eastern and central provinces, but not significant in western provinces. The results of this study have certain reference significance for some countries, where the gap between rich and poor has widened during the epidemic, to narrow the income gap and provide empirical evidence for government decision-makers to give full play to their dividend advantages of digital economy enabling common prosperity. It also provides some ideas for relevant parties who made commitments at the Glasgow Climate Summit (COP26) to curb climate warming and reduce CO2 emissions.